Effectiveness of Clobazam as Add-on Drug in Intractable Epilepsies - Mandal, Pragnadyuti; Ghosh, Souvik; Mondal, Shirsendu; Sanyal, Debasis; Basu, Sagar; Jana, Swapan (Nepal Journal of Neuroscience, 2016)
Twenty to forty percent of patients remain intractable to first line antiepileptic medicines. Clobazam is used as an add-on medicine in treatment of intractable epilepsies.This study evaluated the effectiveness of clobazam as add-on drug in intractable epilepsy patients receiving either valproic acid or carbamazepine.This study is an open label, data based clinical study which was undertaken in a neurology outpatient department of a tertiary care centre.In this study, clobazam was added to epileptic patients who were receiving either valproic acid (VPA) or carbamazepine (CBZ) at maximum clinically tolerated dose. The effectiveness of clobazam was measured by percentages of reduction of seizure frequency from base line (0%, 0-49.9%, 50-99.9%, 100%) and the responder rate (50% or greater reduction of seizure frequency from base line).Fisher’s test and Chi-square test were used for data analysis.Out of total 83 patients (62 male, 21 female, age range 14-60 years, mean age 24.5), 50 and 33 were receiving carbamazepine and sodium valproate respectively. All complex partial seizure (CPS) and 42.3% of generalized tonic clonic seizure(GTCS) patients became seizure free. The responder rate for GTCS cases were 67.3%. The percentages of seizure free patients in VPA and CBZ group were 39.4% and 38% respectively. Seizure frequency reduction and responder rate were found to be significant (p < 0.05) between group.Nepal Journal of Neuroscience 12:26-30, 2015